A comparative study of government policy in dealing with deviant teachings in Islam: The case of Malaysia and Turkey - Asmady Idris; Omer Kurtbag (Human Resource Management Academic Research Society, 2019)
Since the collapse of the Ottoman Empire after World War I, Muslim wilayets (provinces) disintegrated and many were colonialized by the Allied powers comprising the Europeans, Soviet Union and the United States. Post-World War II, however, most of the Muslim wilayets started to achieve their independence and have become part of the modern state system. Muslim states were no longer paying their allegiance to the one single center of leadership as it was during the Islamic Caliphate era. The establishment of the Organization of Islamic Cooperation (OIC) in 1969 could not replace the Caliphate institution for it had no ultimate political power over Muslim countries. Every Muslim country now has their own religious practices. Undeniably, in managing religious affairs they have to deal with a lot of challenges. One of the challenges is the spread of deviant teachings which if no stern action is taken it may threaten the unity of the Muslim community. Meanwhile, Muslim countries have different policies and approaches in tackling the spread of deviant teachings. Therefore, the main aim of this study is to compare Malaysia and Turkey policies in dealing with the deviant teachings within their Muslim community, respectively. The comparative analysis will be revolved around the definition of deviant teachings, government policies and their implications in containing the spread of the deviant teachings in both countries.